Naharaim : Zeitschrift für deutsch - jüdische Literatur und Kulturgeschichte (Journal of German - Jewish Literature and Culture History) (De Gruyter, 2007)
Naharaim is a peer-reviewed journal of the Franz Rosenzweig Minerva Research Centre at the Hebrew University of Jerusalem. It is devoted to current research in philosophical, literary, and historical aspects of German-Jewish culture. The contributions are mainly in German or English.